2019
DOI: 10.1111/and.13344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low androgen status on the expression of adenosine A 2A and A 2B receptors in rat penile corpus cavernosum

Abstract: To investigate whether low androgen status affects erectile function by regulating the expression of adenosine A2A and A2B receptors in rat penile corpus cavernosum. Thirty‐six 8‐week‐old male Sprague‐Dawley rats were randomly divided into six groups: sham‐operated group (4w‐sham, 8w‐sham), castration group (4w‐cast, 8w‐cast) and androgen replacement group (4w‐cast+T, 8w‐cast+T). The rats in the androgen replacement groups were subcutaneously injected with testosterone propionate (3 mg/kg) every other day afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Meanwhile, compared to the control group and castrated+T replacement group, the concentration of NO in the penile cavernous tissue of rat was remarkably decreased in the castrated group. These results indicated that the low androgen level inhibiting the production of NO in the penile carvernous tissue of rat and impaired erectile function; it was consistent with our previous study 22,23 …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Meanwhile, compared to the control group and castrated+T replacement group, the concentration of NO in the penile cavernous tissue of rat was remarkably decreased in the castrated group. These results indicated that the low androgen level inhibiting the production of NO in the penile carvernous tissue of rat and impaired erectile function; it was consistent with our previous study 22,23 …”
Section: Discussionsupporting
confidence: 92%
“…This may result in producing and maintaining penile erection. Our previous study confirmed that inhibition of the AKT/eNOS pathway is one of the molecular mechanisms by which low androgen level impaired erectile function, 25 which was the result of down‐regulating the d level of A2b receptors in penile cavernous tissue of rat with low androgen level 23 . Furthermore, this study found that compared to the control group and castrated+T replacement group, p‐eNOS/eNOS and p‐AKT/AKT in penile cavernous tissue of rat were remarkably decreased in the castrated group.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations